2019
DOI: 10.1111/nep.13225
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and chronic kidney disease association: A systematic review and meta‐analysis

Abstract: Moderate evidence for a positive association between periodontitis and CKD exists. Evidence for the opposite direction is extremely weak based on significant heterogeneity between studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 51 publications
4
78
0
2
Order By: Relevance
“…In the KRAM study, 31% of the females and 25% of the males presented ‘good’ oral hygiene (22). Seventy‐nine per cent of the screened patients had gingival inflammatory diseases; for example, gingivitis or periodontitis and four had M‐A‐S‐H, which is in accordance with the conclusion of the recent systematic review and meta‐analysis finding moderate evidence for a positive association between periodontitis and CKD in international studies (7). In this pilot study, 86% of the patients with CKD carried Candida where the carrier rate in the health population is approximately 50% (23).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the KRAM study, 31% of the females and 25% of the males presented ‘good’ oral hygiene (22). Seventy‐nine per cent of the screened patients had gingival inflammatory diseases; for example, gingivitis or periodontitis and four had M‐A‐S‐H, which is in accordance with the conclusion of the recent systematic review and meta‐analysis finding moderate evidence for a positive association between periodontitis and CKD in international studies (7). In this pilot study, 86% of the patients with CKD carried Candida where the carrier rate in the health population is approximately 50% (23).…”
Section: Discussionsupporting
confidence: 87%
“…Periodontal disease and inflammation have been suggested to be associated with cardiovascular diseases in the general population; however, no causality has been shown (6). A recent systematic review and meta‐analysis concluded that there is moderate evidence for a positive association between periodontitis and CKD (7). Patients with CKD often have comorbidities and among these are hypertension, diabetes mellitus and obesity (8).…”
mentioning
confidence: 99%
“…In China, the most populous country of Asia comprising 20% of worlds’ population, the estimated prevalence of dialysis patients in 2012 was 215 per million population [ 2 ]. Hemodialysis remains the predominant choice of renal replacement therapy over the options of peritoneal dialysis and kidney transplantation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre a saúde bucal de pacientes com DRC têm avaliado a presença de biofilme dental, cálculo e sangramento gengival (BAYRAKTAR et al, 2008;BOTS et al, 2006;BUHLIN et al, 2007), observando também diferentes alterações nos tecidos periodontais destes pacientes (CASTILLO et al, 2007;KAPELLAS et al, 2019;. A presença de doenças periodontais tem sido investigada como uma potencial fonte de inflamação crônica em pacientes com doença renal crônica tratados por hemodiálise (GARNEATA et al, 2015;KSHIRSAGAR et al, 2007) e em pré-diálise (CHANG et al, 2017;NYLUND et al, 2015;SHARMA et al, 2016).…”
Section: Atuação Do Cirurgião-dentista Na Unidade De Terapia Intensivunclassified
“…Na DP ocorre o desequilíbrio da interação entre espécies bacterianas específicas e os componentes da resposta imunológica em indivíduos susceptíveis (GRUBBS et al, 2016), desencadeia uma superexpressão de citocinas próinflamatórias, incluindo a interleucina-1β (IL-1β), interleucina-6 (IL-6), fator de necrose tumoral-α (TNF-α), e subsequente formação de bolsas periodontais e destruição do tecido conjuntivo de inserção e do osso alveolar (FANG et al, 2015;WAHID et al, 2013 Estudos epidemiológicos têm demonstrado que indivíduos com DRC apresentam higiene bucal deficiente e inflamação periodontal (Bayraktar et al, 2008;Castillo et al, 2007;Kapellas et al, 2019; PALAVRAS-CHAVE: resistência, bactéria, profilaxia, odontologia e antimicrobiano.…”
Section: Atuação Do Cirurgião-dentista Na Unidade De Terapia Intensivunclassified